SAT-094 Overweight and Obesity Associated with Immune-Related Adverse Events in Patients on Immune Checkpoint Inhibitor Therapy - Leiter, Amanda (J Endocr Soc, 2019)
Background As immune checkpoint inhibitor (ICI) therapies (PD(L)1 and CTLA-4 inhibitors) are increasingly used for treating malignancy, immune-related adverse events (irAEs) are being encountered by clinicians more frequently. Obesity is a pro-inflammatory metabolic state that has been associated with a higher risk of developing autoimmune disease, but its role in irAEs in patients treated with ICIs is not well characterized. Hypothesis We hypothesized that patients on ICI therapy who were overweight or obese would be more likely to have a grade 2 or greater irAE compared to normal or underweight patients. Methods We retrospectively collected clinical data for 398 cancer patients with baseline body mass index (BMI) data who received ICIs between January 2011 and April 2017 at our institution. Patients were categorized as having lower BMI (low or normal weight, <25) or higher BMI (obese or overweight, ≥25). An irAE was defined as an AE during ICI therapy that was ≥ Grade 2 according to the Common Terminology Criteria for AEs. We compared patient demographic and clinical characteristics between BMI categories. To determine if BMI category was associated with irAEs, we used multivariate logistic regression. Demographics and variables significantly associated with irAEs were included in the model. Results 201 (50.5%) of patients had lower BMI and 197 (49.5%) had higher BMI. 98 patients (24.6%) had an irAE and median follow up time was 8.7 months. The most common malignancies were melanoma (19.6%), non-small cell lung cancer (23.7%), hepatocellular carcinoma (14.6%), and urothelial carcinoma (12.3%). Patients were treated with blockade of CTLA-4 (11.8%), PD1/PDL1, (77.9%), combination of CTLA-4 and PD(L)1 blockade concurrently (4.0%), and sequentially (6.3%). Patients with lower and higher BMI did not differ significantly in respect to age, gender, clinical stage, or category of ICI. Race differed significantly between high vs low BMI categories, (White 60.4% vs 47.3%, Black 8.1% vs 11.9%, Hispanic 11.7% vs 8%, Asian 3.6% vs 11.9%, Unknown/other 16.2% vs 20.9%, p<0.01). Patients with higher BMI were more likely to have a preexisting autoimmune disease (10.8% vs 7.5%, p=0.04). Higher BMI was significantly associated with irAEs (odds ratio (OR) 1.79, 95% confidence interval (CI) 1.09-2.96 in a model adjusted for age, gender, race, ICI category, and preexisting autoimmune disease. Other race (compared to white race) (OR 0.40, 95% CI 0.19-0.83, PD(L)1 blockade (compared to CTLA-4 blockade) (OR 0.49, 95% CI 0.24-0.99), and preexisting autoimmune disease (OR 2.8, 95% CI 1.4-5.7) were also significant predictors of irAEs in the adjusted model. Conclusions Being overweight or obese was associated with irAEs in patients on ICI therapy. Insights into how BMI mediates the immune effects of ICI therapy can potentially elucidate how inflammation plays a role in the metabolic sequelae of obesity and adiposity.